Is FDI into China crowding out the FDI into the European Union? Laura Resmini and Iulia Siedschlag - Laura Resmini; Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2008)
We estimate an augmented gravity model to analyse the effects of FDI into China originating in OECD countries on FDI into EU and other countries over the period 1990-2004. Our results suggest that on average, ceteris paribus, over the analysed period, FDI inflows into China have been complementary to FDI inflows into EU15 countries but they have substituted FDI into the new EU countries in Central and Eastern Europe. In particular, small economies such as Bulgaria and the Baltic countries have been affected negatively by the surge in the FDI into China. This FDI diversion appears in the case of efficiency-seeking FDI.
Keywords: F15; F36; F41; 330; Foreign direct investment; China; European Union; Direktinvestition; OECD-Staaten; China; EU-Staaten; EU-Staaten (Osteuropa)